Peningkatan Penyusunan Laporan Keuangan Berbasis Standar Akuntansi Keuangan EMKM dan Pemeliharaan Keberlanjutan Usaha melalui Pemahaman Akuntansi dan Teknologi Informasi Akuntansi - Nur Fitri Dewi (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
Along with the dynamics of MSMEs in Indonesia, their development faces several problems related to whether the sustainability of MSMEs in Indonesia can be tested in the long term. One of them is caused by capital problems which are often found because MSMEs do not yet have structured financial reports based on SAK EMKM so that they are eligible and accepted when applying for loans. The aim of this research is to determine the influence of understanding accounting and accounting information technology on the preparation of SAK EMKM-based financial reports and their impact on business sustainability for MSMEs in Cilodong, Depok, West Java. The population of this research is MSMEs, Cilodong. The data collection method was a questionnaire distributed to 100 samples of MSMEs in Cilodong, Depok. The collected data was processed using SPSS 27.00 with t test and Path Analysis. The research results show that understanding accounting and accounting information technology has a positive effect on the preparation of SAK EMKM-based financial reports and business sustainability. The results of this research can be useful for MSMEs as input and consideration as well as adding insight, especially regarding the preparation of financial reports and the sustainability of MSME businesses in Cilodong, Depok.